Revision of the Barsine zebrina species-complex, with description of three new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2018)
The Barsine zebrina species-complex is revised. Three new species, Barsine subzebrina Volynkin & Černý, sp. nov. (Nepal, NE India, N Myanmar), Barsine bucseki Volynkin & Černý, sp. nov. (Malay Peninsula) and Barsine navneetsinghi Volynkin & Černý, sp. nov. (NE India and N Myanmar) are described. A new combination is established: Barsine zebrina (Moore, 1878), comb. nov. Adult, male and female genitalia are illustrated.